Mediated Electrochemical Oxidation with Lead as Electrode for Organic Waste Treatment from Pulp Industry: Oksidasi Elektrokimia Termediasi dengan Elektroda Timbal untuk Pengolahan Limbah Organik dari Industri Pulp - Haryono; Juliandri; Rostika Noviyanti, Atiek; Kurnia, Irwan (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2026)
The pulp industry is a type of industry based on natural materials, namely lignocellulose, which produces relatively large amounts of organic liquid waste. The use of various types of synthetic chemicals in the pulp production process results in waste from this industry being classified as hazardous and toxic waste. Various methods of liquid waste treatment can be applied, one of which is the Mediated Electrochemical Oxidation (MEO) method. The MEO method allows organic compounds in liquid waste to be oxidized into simple and relatively environmentally friendly inorganic compounds, such as carbon dioxide and water. The purpose of this study was to determine the effect of the potential difference between electrodes and time on the performance of the MEO method with lead electrodes in the treatment of organic liquid waste from the pulp industry. The potential difference between electrodes was studied at values of 3.0, 4.5 and 6.0 volts, while the electrolysis time in MEO was studied for 60, 90 and 120 minutes. The performance of the MEO method in the treatment of organic liquid waste was determined based on the degradation efficiency parameters. The results showed that the maximum degradation efficiency of organic waste was achieved when MEO was carried out at a potential difference between electrodes and an electrolysis time of 6.0 volts and 120 minutes. Under these MEO operating conditions, an organic waste degradation efficiency of 99.03% was achieved. AbstrakIndustri pulp merupakan salah satu jenis industri berbasis bahan alam, yaitu lignoselulosa, yang menghasilkan limbah cair organik relatif banyak. Pemanfaatan berbagai jenis bahan kimia sintetik pada proses produksi pulp mengakibatkan limbah dari industri tersebut termasuk sebagai limbah berbahaya dan beracun. Berbagai metode pengolahan limbah cair dapat diterapkan, salah satunya adalah metode Oksidasi Elektrokimia Termediasi (OET). Metode OET memungkinkan senyawa organik pada limbah cair untuk dioksidasi menjadi senyawa anorganik sederhana dan relatif ramah lingkungan, seperti karbon dioksida dan air. Tujuan penelitian ini adalah menentukan pengaruh beda potensial antar elektroda dan waktu terhadap kinerja metode OET dengan elektroda timbal pada pengolahan limbah cair organik dari industri pulp. Beda potensial antar elektroda dipelajari pada nilai 3,0, 4,5 dan 6,0 volt, sedangkan waktu elektrolisis pada OET dipelajari selama 60, 90 dan 120 menit. Kinerja metode OET pada pengolahan limbah cair organik ditentukan berdasarkan parameter efisiensi degradasi. Hasil penelitian menunjukkan bahwa efisiensi degradasi limbah organik maksimum dicapai ketika OET dilakukan pada beda potensial antar elektroda dan waktu elektrolisis sebesar 6,0 volt dan 120 menit. Pada kondisi operasi OET tersebut dicapai efisiensi degradasi limbah organik sebesar 99,03%.